(3JhQGI HQGgeG (B:s (3TQjYI GdgfOhS (B: (3OQGSI ebGQfI (B/s - (3GdMGjc, efPQs 1944- ((3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3UaMGJ ddOQGSGJ hGdfTQ hGdJhRjY,s, 2020)
"(3HGdQZe ef hLhO cKjQ ef GdeOGQS GdacQjI, hGfJTGQ YOO ef GdCOjGf aj GdUjf, EdG Cf GdchfahTjI cGfJ OGFeG GdCcKQ JCKjQG aj GdKbGaI hGdSjGSI hGdEOGQI GdUjfjI(B. (3hHGdQZe ef cd GdMedGJ GdTQSI GdJj TfJ VOgG abO JecfJ GdchfahTjI ef GdGSJeQGQ aj GdhLhO dJchf PGJ JCKjQ hGVM aj acQ GdeLJeY GdUjfj GdeYGUQ hSdhcg(B. (3hGdjhe HYO GdfghV GdGbJUGOj GdcHjQ ddUjf, hQZHI GdYGde GdeJRGjOI aj GdJYGed eY GdUjfjjf, aEffG fQi Cf gPG GdJYGed jchf CjSQ hCaVd YfO eYQaI GdechfGJ GdacQjI hGdCNdGbjI hGdOjfjI ddUjfjjf, hfYJbO HCf EfLjd chfahTjhS jTcd CaVd eLGd dgPg GdeYQaI(B. (3Ef EfLjd chfahTjhS gh YfhGf GdcJGH GdChd ef eLehYI GdcJH GdJj Je efgG GNJjGQ fUhU gPG GdcJGH, hgj fUhU OhfJ HEjLGR hhVhM BQGA cfahTjhS hCbhGdg ceG PcQgG CJHGYg, jJVef eMJhGgG GdSdhc hGdeYGedGJ HTcd YGe(B. (3ceG JYO ef GdcJH GdCcKQ JCKjQG aj GdKbGaI GdUjfjI efP YUQ chfahTjhS hMJi GdBf(B." s
(3GdETQGa GdYGe (B: (3jRf jYbhH(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdHgGZGaGO ZjJGs; (3GdgfOhSjIs